TaSPL13 regulates inflorescence architecture and development in transgenic wheat (Triticum aestivum L.). (July 2020) - Li, Li; Shi, Fu; Wang, Yaqiong; Yu, Xiaofen; Zhi, Jingjing; Guan, Yanbin; Zhao, Hongyan; Chang, Junli; Chen, Mingjie; Yang, Guangxiao; Wang, Yuesheng; He, Guangyuan
Highlights: Expression patterns of TaSPLs in different tissues of wheat by RNA-seq. TaSPL13-2B transgenic rice showing increased panicle branches with more grains. TaSPL13-2B transgenic wheat with significant increases in florets and grains per spike. Abstract: The SQUAMOSA promoter-binding protein-like (SPL) proteins play vital roles in plant growth and development in rice ( Oryza sative L.) and Arabidopsis thaliana (L.) Heynh. However, few studies regarding the SPL proteins have been reported in wheat. In this study, 56 TaSPLs were clustered into eight groups according to an OsSPL phylogenetic comparison analysis. The expression patterns of TaSPLs in different tissues were analysed by RNA-seq data, and partial results were confirmed by qRT-PCR. Based on the above results, genes such as TaSPL13 and TaSPL15 may be involved in spike or seed development in wheat. Multiple genes that regulate the inflorescence architecture of rice have been identified. Additionally, studies on the genes associated with spikelet development in wheat have been reported relatively rarely. Here, TaSPL13-2B was transferred into wheat cv . Bobwhite. Compared with the wild type, the transgenic lines showed significant increases in the number of florets and grains per spike, indicating that TaSPL13-2B could influence the floret development of wheat. TaSPL13-2B was transferred into rice cv . Nipponbare, which demonstrated that TaSPL13-2B can modify panicle architecture in transgenic rice, with significant increases in panicle length, the number and length of primary branches, and the number of secondary branches.